DNA mismatch repair activity of MutLα is regulated by CK2‐dependent phosphorylation of MLH1 (S477). Issue 12 (5th September 2018) - Weßbecher, Isabel M.; Hinrichsen, Inga; Funke, Sebastian; Oellerich, Thomas; Plotz, Guido; Zeuzem, Stefan; Grus, Franz H.; Biondi, Ricardo M.; Brieger, Angela
Abstract : MutLα, a heterodimer consisting of MLH1 and PMS2, is a key player of DNA mismatch repair (MMR), yet little is known about its regulation. In this study, we used mass spectrometry to identify phosphorylated residues within MLH1 and PMS2. The most frequently detected phosphorylated amino acid was serine 477 of MLH1. Pharmacological treatment indicates‎ that Casein kinase II (CK2) could be responsible for the phosphorylation of MLH1 at serine 477 in vivo. In vitro kinase assay verified MLH1 as a substrate of CK2. Most importantly, using in vitro MMR assay we could demonstrate that p‐MLH1 S477 lost MMR activity. Moreover, we found that levels of p‐MLH1 S477 varied during the cell cycle. In summary, we identified that phosphorylation of MLH1 by CK2 at amino acid position 477 can switch off MMR activity in vitro. Since CK2 is overexpressed in many tumors and is able to inactivate MMR, the new mechanism here described could have an important impact on tumors overactive in CK2.